Genetic variants related to successful migraine prophylaxis with verapamil. Issue 6 (7th April 2021) - Cutrer, Fred Michael; Moyer, Ann M.; Atkinson, Elizabeth J.; Wang, Liguo; Tian, Shulan; Wu, Yanhong; Garza, Ivan; Robertson, Carrie E.; Huebert, Carey A.; Moore, Brenda E.; Klein, Christopher J.
Abstract: Background: Currently, there is no biologically based rationale for drug selection in migraine prophylactic treatment. Methods: To investigate the genetic variation underlying treatment response to verapamil prophylaxis, we selected 225 patients from a longitudinally established, deeply phenotyped migraine database ( N = 5983), and collected uninterrupted quantitated verapamil treatment response data and DNA for these 225 cases. We recorded the number of headache days in the four weeks preceding treatment with verapamil and for four weeks, following completion of a treatment period with verapamil lasting at least five weeks. Whole‐exome sequencing (WES) was applied to a discovery cohort consisting of 21 definitive responders and 14 definitive non‐responders, and the identified single nucleotide polymorphisms (SNPs) showing significant association were genotyped in a separate confirmation cohort (185 verapamil treated patients). Statistical analysis of the WES data from the discovery cohort identified 524 SNPs associated with verapamil responsiveness ( p < 0.01); among them, 39 SNPs were validated in the confirmatory cohort (n = 185) which included the full range of response to verapamil from highly responsive to not responsive. Results: Fourteen SNPs were confirmed by both percentage and arithmetic statistical approaches. Pathway and protein network analysis implicated myo‐inositol biosynthetic and phospholipase‐C second messenger pathways in verapamil responsiveness, emphasizing the earlier pathogenic understanding of migraine. No association was found between genetic variation in verapamil metabolic enzymes and treatment response. Conclusion: Our findings demonstrate that genetic analysis in well‐characterized subpopulations can yield important pharmacogenetic information pertaining to the mechanism of anti‐migraine prophylactic medications. Abstract : Whole exome sequencing in 21 definitive verapamil responders and 14 definitive non‐responders identified 524 SNPs showing significant ( p < 0.01) association with verapamil responsiveness. Genotyping the 524 significant SNPs in 185 other verapamil treated patients identified 39 validated SNP's. Pathway analysis based on the 39 significant SNPs implicated the related myo‐inositol and phospholipase‐C second messenger pathways in verapamil responsiveness.